Comparative study of meningeal enhancement in canine and feline otitis media-interna: 3D-gradient-echo vs. fat-suppressed turbo-spin-echo-T1-weighted sequences in MRI - Graf, Florian; Dennler, Matthias; Beckmann, Katrin; Mauri, Nico; Makara, Mariano; Wang-Leandro, Adriano (Frontiers in Veterinary Science, 2025)
MRI plays an important role in diagnosing meningeal disease in dogs and cats. It remains unclear which T1 sequence most reliably detects meningeal contrast enhancement. The aim of this retrospective study was to compare detection rate, inter- and intra-observer agreement of meningeal enhancement in otitis media-interna between 3D-GRE-T1W and transverse FS-TSE-T1W sequences. MRI studies of dogs and cats with otitis media and interna from 2017 to 2023 including both sequences of interest were collected and supplemented with a control group. Five observers assessed presence or absence of meningeal enhancement twice independently in each sequence and blinded to the diagnosis. Detection rate, inter- and intra-observer agreement were evaluated using Student's T-Test and Fleiss' Kappa test, respectively. Cases from 46 dogs and 74 cats and 21 control cases met the inclusion criteria. On average, the observers detected meningeal enhancement significantly (p < 0.01) more often in the FS-TSE-T1W than in the 3D-GRE-T1W sequence. Significance applied only to cats, but not to dogs. They reached a substantial inter-observer agreement in both sequences (kappa values of 0.701 and 0.735) and a substantial intra-observer agreement independent of the sequence. These results show that highlighting diseased meninges with fat saturation contributes more than a reduction of volume-average artifacts by increasing resolution in the detection of meningeal enhancement in cats and dogs with otitis media and interna. However, over-interpretation of normal meningeal appearance is possible.